Gas Turbine Unit Type (GE FRAME 9E) The Component of Unit and The Fundamentals of Operation Sequence- A Training Course for New Employees - Kadhim KASHI (Global Scientific Publishing, 2024)
The evolution of energy generation, from coal to oil to nuclear and now renewable sources, has shaped the global energy landscape. With a growing emphasis on environmental protection and diversification of energy sources, gas turbines have emerged as a prominent player. This paper focuses on the gas generating unit type (GT F9E) manufactured by GE, aiming to inform engineering and technical personnel about its components, operation, and qualifications required for personnel. The research addresses the need to equip new cadre in power plants with knowledge and training for optimal operation of these units. Details include the unit's specifications such as compressor and turbine stages, combustion chambers, and operational principles. Components like the intake air system, compressor, combustion system, turbine, exhaust system, and support system are explained, along with their functions. The gas stream path, from intake to exhaust, is delineated to provide a comprehensive understanding of the unit's operation
Keywords: Turbine; Iraq; Replenishment